The open economy balance sheet channel and the exporting decisions of firms: evidence from the Brazilian crisis of 1999 - Bougheas, Spiros; Mizen, Paul; Silva, Simone (Oxford University Press, 2015)
We consider the impact of the Brazilian crisis of 1999 on the extensive and intensive margin of exporters versus non-exporters through the open economy balance sheet channel. Using an open economy balance sheet channel model with firm heterogeneity, we explore predictors that firms will engage in global markets. Our results based on a detailed firm-level panel of data for Brazilian 10,573 firms for the period 1996–2007, show that the decision to export and overall growth of sales for exporting firms is driven by size, the debt ratio, the current ratio and operating costs as well as the direct impact of the crisis itself. The findings suggest that the mechanism is driven by the response of the credit market to the creditworthiness of firms as it is by changing terms of trade.